Rent control in the Philippines: An update - Marife M. Ballesteros; Tatum P. Ramos; Jasmine E. Magtibay (Philippine Institute for Development Studies (PIDS), 2016)
Rent control was introduced in the Philippines in 1971 to stabilize the prices of basic commodities during periods of calamities and macroeconomic instability. It has been adopted in succeeding years despite the country's exit from the highly inflationary environment. Rent control-related policies, however, have had adverse impacts on the rental market. Consequently, the Philippine government has made changes to the original rent control setup; there was a move from the first to the second generation rent control. This study specifically determines whether second generation rent control is indeed free of the adverse impacts of its predecessor. It uses the 2014 Annual Poverty Indicators Survey to have an estimation of the net benefit of tenants under rent control.
Keywords: 330; second generation rent control; rental market